Knowledge and Competence of Agricultural Extension Field Workers in Farmer-Group Facilitation in Kwara State, Nigeria - Kemi Funmilayo Omotesho; Blessing Akinola-Soji; Gbolagade Benjamin Adesiji; Oluwasanjo Biodun Owojaiye (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2021)
The weakness of most farmer-groups in Nigeria has been linked to poor group facilitation by field agricultural extension workers. The study assessed the knowledge and competence of extension officers in group facilitation. A two-stage random sampling technique was used to select 174 farmers on which a structured interview schedule was administered. A questionnaire was administered on all 69 field extension workers in the study area. Descriptive statistics, regression analysis, Pearson's Product Moment Correlation and t-test were used for data analyses. Results reveal that 65.2% of extension workers had good knowledge of group facilitation. Farmers rated extension workers lower (mean = 2.36) than the workers rated themselves in group facilitation (means = 3.12). Work experience of extension workers and their access to training in group dynamics significantly influenced workers' competence at P < 0.05. There was a significant relationship between the knowledge and competence of extension workers at p < 0.05 (r = 0.843). The study assessed extension workers' competence in group facilitation using both self and farmers' assessments, identifying specific areas of deficiencies in knowledge and competence.